Dynamic environmental zoning using the CA–Markov model and multicriteria analysis in a Brazilian Cerrado Watershed - Vick, Erivelton Pereira; Machado da Silva, Bruno Henrique; de Souza Amede Sato, Amanda Ayumi; Ribeiro de Oliveira, Víncler Fernandes; da Cunha, Elias Rodrigues; da Rocha Lima, César Gustavo [UNESP]; Bacani, Vitor Matheus (Elsevier, 2024)
The Brazilian Cerrado is considered a hotspot for biodiversity conservation. However, in recent decades, the intensification of human activities, directly influencing changes in use and coverage, has caused severe environmental problems. Thus, this study proposed a dynamic environmental zoning model for the Pântano River watershed (PRW) based on the CA-Markov model and Multicriteria Analysis. The methodological procedures were based on predictive modeling of land use and land cover, analysis of environmental fragility, and estimation of soil losses and sediment delivery rate from the InVEST model for the years 1984, 2007, 2013, 2020, 2030, and 2050. The results showed that over the time analyzed and projected, in the category of Legal Restrictions Zone, there was a slight decrease in the extension of Permanent Preservation Areas, while the Natural Vegetation cover increased considerably, indicating possible changes in the environmental patterns of the region. The areas classified as Plains maintained minimal variations throughout the period studied. With regard to the Rural Productive Zone, there was a notable increase in areas with Low Restriction, suggesting an expansion of less restrictive agricultural and land use activities. On the other hand, the areas with Medium and High Restrictions showed decreasing trends, signaling possible improvements in environmental management and conservation of natural resources. Also noteworthy is the significant reduction in areas classified as High Restriction, associated with the high rate of soil loss. This trend is particularly relevant as it indicates practical efforts to mitigate adverse environmental impacts and promote sustainable soil management practices. Finally, the areas designated as Special Protection Zones, including Incongruities and Reservoirs, remained stable throughout the period analyzed, demonstrating the importance of preserving these areas to conservation of biodiversity and water resources. In conclusion, the results obtained in this study contribute to guiding public policies and environmental management practices in the PRW region. The observed trends indicate a positive evolution towards the conservation and sustainable use of natural resources, underscoring the importance of continuous measures to ensure the health and resilience of local ecosystems.
Keywords: Ecosystem conservation; Environmental management; InVEST Model; Land use; Predictive modeling; Watershed